Harbor nocturne [compact disc, unabridged] - Wambaugh, Joseph (Highbridge Audio, 2012)
When Dinko Babich, a young longshoreman, delivers Lita Medina, a young Mexican dancer, from San Pedro Harbor to a Hollywood nightclub, their lives are forever changed. An unexpectedly tender and moving love story develops among the cops and criminals who occupy the harbor, and soon Dinko and Lita are caught up in terror and peril through no fault of their own.